Sustainability of Food and Dessert Culture in Yozgat Region / Yozgat Yöresi Yemek ve Tatlı Kültürünün Sürdürülebilirliği - Selma Korkmaz; Tülay Kaya Tekman (Folklor/Edebiyat, 2021)
Yozgat is a city that both allows and gives a lot of immigrants. As it is allowing and giving a lot of immigrants, it is a matter of curiosity whether the people of Yozgat maintain their cultural values or not. The aim of this study is to reveal if the people of Yozgat know their food and dessert culture. The sample of the study consists of 50 women who are originally from Yozgat but some of them live there, some of them live in different cities in Turkey and some of them live abroad. During the creation of the data collection tool, a total of 8 questions consisting of 5 main and 3 sub-questions were prepared by getting the opinioıns of 3 public educators. Thus, an interview form consisting of 8 questions was used in data colection. Through this interview form, by considering the age and working status variables, it has been revealed how much the women from Yozgat know about the food and dessert culture of Yozgat. In analyzing the obtained data, content analysis was used and the data were devided into certain categories and themes, shown as frequency and percentages, and various comparisons were made. The results of the study showed that the women between the ages of 46-70 know more about the food and dessert culture of Yozgat than women between the ages of 20-45. In addition to this, it was found out that the women who do not work know the food and dessert culture more than those who work.